High grade endometrial stromal sarcoma: a clinician dilemma - Dogra, Poojan; Sharma, Shuchi; Sharma, Reena; Bhardwaj, Suraj (International Journal of Research in Medical Sciences, 2021)
Uterine sarcomas are relatively rare tumors of mesodermal origin. ESS occurs primarily in perimenopausal women in 4th and 5th decade of their life; about one third occurs in postmenopausal women. Here in we describe a case of 44 years old patient presented with one month history of foul smelling discharge per vagina and a pelvic mass. Ultrasound and MRI gave possibility of a large anterior wall and fundal fibroid with degeneration versus neoplastic endometrial thickening. The patient underwent exploratory laparotomy with total abdominal hysterectomy with bilateral salpingoophorectomy with pelvic lymphadenectomy. Histopathology showed tumor cells with round to oval nuclei with high mitotic activity, blood vessel proliferation between the tumor cells and extensive lymphovascular invasion. The pathological diagnosis was HG-ESS stage IB. The patient was referred to radiotherapy department for adjuvant therapy. HG-ESS is a rare clinical entity and considered as important differential diagnosis.